Shortest Path Detection among the Clustering Nodes (International Journal of Engineering and Computer Science, 2018)
The main objective of this paper is to select the  module first we need to provide source and destination addresses at source and destination IP address filed respectively .Next we need to select the node that needs to be sent to destination using the select button. If we want to know the shortest path among the clustering nodes  first all the nodes will be sent to destination by selecting the node at server side .server side node will be sent to receiver side where we can calculate the time and speed. previous existing system consumes more time. To overcome this problem I am calculating the shortest time between the nodes.In this module I am selecting the destination for sending the node at server side. If the current node is not in the destination again browse the node and selecting the path then it will display shortest path among the nodes.